The preinterventional psychiatric history as a major predictor for a reduced quality of life after treatment of unruptured intracranial aneurysms - Fontana, Johann; Groden, Christoph; Schmieder, Kirsten; Wenz, Holger (World neurosurgery, 2015)
A significantly increased rate of positive preinterventional psychiatric histories in the unruptured aneurysm collective was demonstrated previously. The current study was designed to analyze the influence of the preinterventional psychiatric status on the outcome after treatment of unruptured intracranial aneurysms. Patients treated due to meningioma World Health Organization °I and unruptured intracranial aneurysms in 2 German neurosurgical centers between 2007 and 2013 were screened for exclusion criteria including malignant/chronic diseases, recurrence of the tumor/aneurysm, and neurologic deficits among others. The preinterventional psychiatric histories and the rates of postinterventional headaches, sleeping disorders, symptoms of chronic fatigue syndrome, and quality of life (QOL) were determined by questionnaires that were mailed to the patients in a printed version. A total of 58 M patients and 45 iA patients who met the inclusion criteria returned the questionnaires; 10 M (17.2%) and 17 iA patients (37.8%) had a positive psychiatric history. The overall Incidental aneurysm collective demonstrated significantly lower overall QOL scores (P = 0.003) and significant greater rates of chronic fatigue syndrome (P = 0.009) compared with the M collective. After we excluded all patients with positive pre-interventional psychiatric histories, those differences were no longer reproducible. Subjectively, the patients did not realize any significant changes in their QOL after successful aneurysm treatment. The results of the current study demonstrate the importance of taking the preinterventional psychiatric history into considerations when evaluating the outcome after unruptured aneurysm treatment. The unfavorable outcome of the aneurysm group seems to be caused by factors that are not related the aneurysm diagnosis or treatment itself.